Bempedoic Acid for Heterozygous Familial Hypercholesterolemia: From Bench to Bedside - Agarwala A; Quispe R; Goldberg AC; Michos ED (Dove Medical Press, 2021)
Anandita Agarwala,1 Renato Quispe,2 Anne C Goldberg,3 Erin D Michos2 1Division of Cardiology, Baylor Scott and White Health, Heart Hospital Baylor Plano, Plano, TX, USA; 2Ciccarone Center for the Prevention of Cardiovascular Disease, Division of Cardiology, Department of Medicine, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 3Division of Endocrinology, Metabolism and Lipid Research, Washington University School of Medicine, St. Louis, MO, USACorrespondence: Erin D MichosCiccarone Center for the Prevention of Cardiovascular Disease, Johns Hopkins Hospital, 600 N. Wolfe Street, Blalock 524-B, Baltimore, MD, 21287, USATel +410-502-6813Email edonnell@jhmi.eduAbstract: Bempedoic acid is a first-in-class, oral, inhibitor of cholesterol biosynthesis that is approved for use in patients with atherosclerotic cardiovascular disease (ASCVD) and for primary prevention in individuals with heterozygous familial hypercholesterolemia (HeFH) by the United States Food and Drug Administration. Pooled data from the phase III clinical trials, CLEAR Harmony and CLEAR Wisdom, have demonstrated the safety and efficacy of bempedoic acid with regard to lowering of low-density lipoprotein cholesterol (LDL-C) in patients with HeFH as an adjunct or alternative to currently existing lipid-lowering therapies. CLEAR Outcomes is a cardiovascular outcomes trial that is currently underway that will provide additional insight as to where bempedoic acid will fit into treatment regimens among the non-statin lipid-lowering therapy options. Patients who might particularly benefit from bempedoic acid are those with HeFH and those unable to take adequate doses of statins or take any statin therapy altogether who need additional LDL-C lowering. In this review, we will discuss the profile of bempedoic acid from its design, development, and its place in therapy for the management of LDL-C for the purposes of ASCVD prevention.Keywords: bempedoic acid, familial heterozygous hypercholesterolemia, lipids, atherosclerotic cardiovascular disease, prevention, low-density lipoprotein cholesterol